Evaluation of black soldier fly larvae oil as a feed ingredient for broiler chickens: effects on performance, carcass traits, meat characteristics, and blood parameters - Somparn, Nantanant; Pootthachaya, Padsakorn; Puangsap, Warin; Pintaphrom, Nisakon; Srikha, Theeraphat; Tengjaroenkul, Bundit; Cherdthong, Anusorn; Wongtangtintharn, Sawitree (Frontiers in Animal Science, 2024)
The aim of the present study was to evaluate the effects of replacing diet rice bran oil (RBO) with black soldier fly larva oil (BSFLO) on the growth performance, carcass traits, meat quality, and blood parameters of broiler chickens. At one day of age, a total of 180 male broiler chickens (Ross 308) were randomly allocated to 3 experimental groups (4 replicates and 15 birds/pen). To a basal control diet, either 50% or 75% of the RBO was replaced with BSFLO, respectively. The growth performance was monitored throughout the rearing period (divided into 3 periods: 1-10, 11-24, and 25-42 days). On days 24 and 42, Blood samples were taken from each treatment for hemato-biochemical index determination. At the termination period, 8 birds (two birds/pen) per group were slaughtered for carcass and meat quality measurement. Samples of the liver were submitted for fatty acid investigations. The results showed that the inclusion of 75% BSFLO in the broiler diet significantly increased FCR (Feed conversion ratio) in the finisher and overall periods. Interestingly, replacing 50% of RBO with BSFLO did not influence growth performance, carcass traits, and hematochemical parameters compared to 75% of BSFLO and control groups. The present study suggests that partially replacing RBO with 50% of BSFLO in broiler chicken diets has no adverse effects on growth performance, carcass-meat quality, or blood parameters.